2016
DOI: 10.4236/health.2016.813141
|View full text |Cite
|
Sign up to set email alerts
|

Practical Use of Stairs to Assess Fitness, Prescribe and Perform Physical Activity Training

Abstract: Aim: Evaluating climbing stairs for prescription and implementation of physical activity regimes. Methods: Healthy females (F, n = 14), and males (M, n = 15) participated. By climbing 100 steps of stairs with 0.173 m height, Heart rate (HR) and oxygen uptake were measured throughout the floors; Blood pressure (BP) was measured at ground and the 5th floors only. Results: Energy increased from 2 to 7.6 was metabolic equivalents (METs = 3.5 ml O 2 /min•kg) at 17.3 m elevation in 2 min. at the 5th floor, and perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…Several studies involving young intact subjects, such as the ones recruited for the present work, reported that the subjects experienced an increased energy expenditure when ascending the stairs with respect to descending phases [39][40][41][42][43]. Furthermore, as stair walking is more cognitively demanding than level walking [44], also the specific task of ascending or descending the stairs may require different attentional resources.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Several studies involving young intact subjects, such as the ones recruited for the present work, reported that the subjects experienced an increased energy expenditure when ascending the stairs with respect to descending phases [39][40][41][42][43]. Furthermore, as stair walking is more cognitively demanding than level walking [44], also the specific task of ascending or descending the stairs may require different attentional resources.…”
Section: Discussionmentioning
confidence: 84%
“…The energy cost of ascending stairs is considerably higher than descending stairs and walking overground [39][40][41][42][43] and requires a greater demand of attentional resources, even in unimpaired subjects [44]. The different physical and cognitive effort associated with the specific motor task performed might affect the perceived intuitiveness and comfort of the haptic feedback, biasing the rating of the stimulation strategies assessed by the subjects.…”
Section: Introductionmentioning
confidence: 99%
“…For men or athletes, exercising up and down stairs should be adjusted to the conditions, to maintain health recommended 600 MET.min/week with an average exercise intensity of 6 MET, 100 minutes/week divided by 20 minutes/day. By adjusting the floor height, speed, repetition and controlling the pulse, going up and down the stairs will be safely used as a model of physical activity and exercise training [8].…”
Section: Discussionmentioning
confidence: 99%
“…Es una opción económica que provee entrenamiento aeróbico y de resistencia sin la necesidad de equipos especializados (4,17). Aunque ninguno de los participantes tenía hipertensión arterial diagnosticada y tampoco mostraron valores de PAM patológicos, se deben monitorizar la presión arterial, ya que elevaciones de la presión arterial sistólica durante la escalada por encima de 140 mmHg, que disminuyan la presión arterial diastólica o que la aumenten a valores más altos que en reposo pueden indicar una patología (18).…”
Section: Discussionunclassified